Cases of aspergillosis in Javan Hawk-eagle (Spizaetus bartelst): Isolation of the causative agents and the pathological changes of the diseas - Hastiono, Sukardi; Damayanti, Rini; Gholib, Djaenudin (Indonesian Journal of Animal and Veterinary Sciences, 1995)
Two cases of aspergillosis in Javan Hawk-eagle (Spizaetus banelsi) from Safari Garden of Indonesia, Cisarua, Bogor, have been reported . Specimens of lungs, airsacs, livers, spleens, kidneys, and intestines were examined mycologically and pathologically . Mycological examination revealed in the isolation of the causative agents from lungs and airsacs, ie . Aspergillus niger from one bird, and Aspergillusfianigarus from the other one . Pathological anatomy examination showed formation of yellowish white miliary nodule lesions, especially in the lungs and airsacs, while histopathological examination showed congestion and granulomatous tissue formation in the lungs, ie . specific lesion of mycotic infection with necrotic zone in the centre, surrounded by lymphocytes, macrophages, fibrin, and fungal hyphae . Pathological changes of the other organs were also described . These findings were the first officially description of aspergillosis cases in these carnivorous birds . Key words: Javan Hawk-eagle, Spizaetus battelsi, aspergillosis, Aspergillus niger, Aspergillus fumigatus